Impact of Knowledge and Practice on Fasting Blood Glucose Levels among Diabetics During Ramadan Fasting - Mohammed Al-Hariri; Soban Khan; Walid Albaker; Waleed Al Malik (Springer, 2019)
The aim of the present study was to investigate the impact of knowledge and practice on the fasting blood glucose of diabetic patients during the month of Ramadan. The simple random sampling technique was used to calculate sample size and the computed sample size was 112. Participants were recruited from the diabetic outpatient clinics at King Fahad Hospital of the University, Dammam, Saudi Arabia. The participants included male and female adults with either type 1 or 2 diabetes, aged 15-70 years. Children, pregnant women, and those who were unable to complete at least 3 weeks of fasting during the study period were excluded from the study. Fasting blood glucose reading of the participants was extracted during Ramadan and in Shawwal (after 30 days) and a first-visit questionnaire related to the knowledge and practice was provided to them. Statistical Package for Social Sciences (version 22) was used for data entry and analysis. A two way ANOVA test, two independent sample t-tests and Chi-square test were used to compare between the groups. A p-value at 0.05 was considered statistically significant. The study found that fasting blood glucose of a participant during the holy month of Ramadan (144.2) was statistically significant with p-value 0.0003 as compared with after Ramadan (178.5). Moreover, it was found that as the level of knowledge (poor, average, good) improved, the fasting blood glucose goes down with p-values 0.036 and 0.037. Our results revealed that fasting during Ramadan significantly decreases blood glucose. The overall level of knowledge and practice concerning diabetes among the participants studied during the month Ramadan is average.